Penerapan Tugas Proyek Botani dalam Upaya Pembentukan Keterampilan Kerja Mahasiswa - Marthinus, Vonnisye; Tandirerung, Willy Yavet; Marewa, Jens Batara (JURNAL KONSELING GUSJIGANG, 2023)
Collaboration, communication, and creativity are all work qualities that must be had by someone. These abilities, however, are still missing in students who will graduate and be ready to work. Students will work together in groups to complete tasks, becoming acclimated to working in teams, communicating in teams, and expanding their creativity in the process. The goal of this study is to use project assignments in the classroom to help students enhance their collaboration, communication, and creativity skills. The Nonequivalent Post Test Only Control Group Design is used in this type of study to create a quasi-experimental design. The experimental class and the control class were employed as research samples in this study. Students' collaboration, communication, and creativity skills in the experimental class were higher than in the control class, according to descriptive statistical analysis. Implementing tasks has an influence on developing students' communication abilities and creativity, according to inferential statistical research. In terms of collaboration skills, it appears that they have little bearing on the execution of project duties.